2008
DOI: 10.1002/jbm.a.32199
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic delivery system using nano‐hydroxyapatite/chitosan bone cement consisting of berberine

Abstract: Different concentrations of berberine were mixed with nano-hydroxyapatite/chitosan (n-HA/CS) bone cement to generate an antibiotic drug delivery system for treatment of bone defects. Properties of the system such as setting time, compressive strength, surface morphology, phase compositions, drug release profiles and antimicrobial activity were also characterized. It was shown that the setting time of the cement ranged from 17.03 +/- 0.50 min to 28.47 +/- 0.96 min and the compressive strength changed from 184.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…Chitosani sal inear polymer composed of glucosamine (2amino-2-deoxy-d-glucopyranose), and is ac ationic polymer that is soluble in weakly acidic solution.C hitosan is ab iocompatible and biodegradable, pH-dependent cationicp olymer, which has become one of the most promising biopolymers for applicationsi nd rug delivery,t heranostics, gene therapy,a nd tissue engineering. [9] Combined with the advantageso fH AP, variousk inds of HAP/chitosan (HAP/CS) composite biomaterials, such as HAP/CS composite nanofibers, [10] scaffolds, [11] bone cements, [12] hydrogels, [13] and membranes, [14] have been synthesized and investigated for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosani sal inear polymer composed of glucosamine (2amino-2-deoxy-d-glucopyranose), and is ac ationic polymer that is soluble in weakly acidic solution.C hitosan is ab iocompatible and biodegradable, pH-dependent cationicp olymer, which has become one of the most promising biopolymers for applicationsi nd rug delivery,t heranostics, gene therapy,a nd tissue engineering. [9] Combined with the advantageso fH AP, variousk inds of HAP/chitosan (HAP/CS) composite biomaterials, such as HAP/CS composite nanofibers, [10] scaffolds, [11] bone cements, [12] hydrogels, [13] and membranes, [14] have been synthesized and investigated for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, moist exposed burn ointment (MEBO), a Chinese burn ointment with a USA patented formulation since 1995, which was developed at the China National Science and Technology Centre in Beijing in 1989 (23,24), has been used to treat thickness burns in clinical practice and has achieved beneficial efficacy (25)(26)(27)(28) (30) and that berberine exhibits antimicrobial effects (31). Clinical and experimental studies have shown that MEBO exhibits analgesic and antimicrobial effects, and reduces the treatment time of burns (25)(26)(27)(28)32,33).…”
Section: Introductionmentioning
confidence: 99%
“…The release kinetics of 27% HACC from the nanotubes was determined by the anthrone sulfuric acid reaction [29,34,35]. Three discs of NT-H with different diameters were each individually immersed in 1 ml of PBS in a 48-well plate (Costar3548, Corning Incorporated, Corning, NY, USA) at a temperature of 37 °C and agitated at 100 rpm.…”
Section: Methodsmentioning
confidence: 99%